A systematic review. Current understanding of the infection caused by Betapolyomavirus hominis - D. R. Prilepskaya; E. A. Domonova (Журнал инфектологии)
Reactivation of Betapolyomavirus hominis (BKPyV) in kidney and hematopoietic stem cell recipients can lead to serious complications such as BKPyV-associated nephropathy followed by transplant rejection and BKPyV-associated hemorrhagic cystitis. Early diagnosis of the disease is hampering by the possible combination of infection of BKPyV with other post-transplant pathologies and the absence of specific symptoms. Replication of BKPyV is currently the only reliable prognostic sign of the development of long-term consequences, so patient management is basseting on monitoring the concentration of viral DNA. However, consistency between the results of determining the viral load and the development of post-transplant complications associated with BKPyV reactivation cannot be achieving without effective means of standardizing laboratory testing. This review covers the current understanding of the epidemiology; pathogenesis and the clinical features of the disease associated with BKPyV, and also considers in detail the current methods of laboratory diagnosis infection of BKPyV.